COMPLIMENTS AND COMPLIMENT RESPONSES IN YOUTUBE COMMENTS - Nanda Ulfa; Sigit Haryanto; Titis Setyabudi (STKIP Siliwangi, 2023)
This study investigated types of compliments used by netizen and the responses towards the compliments found in YouTube comments. Qualitative descriptive research methods was employed in this study. The data source comes from Youtube Comments on the NFL's web page entitled Rihanna's Full Apple Music Super Bowl LVII Halftime Show. The data was collected by using documentation and then analyzed by using content analysis. The findings revealed that there were three types of compliments found in the comments such as 7 appearances (7), skill / abilities (16) and personalities (2). It can be concluded that ability compliment was the most frequent appearing of compliments types. In addition, the data also showed that there were six compliment strategies found in the comments such as 5 Comment acceptance, 1 reassignment, 2 return, 1 question, 2 disagreements and 1 request interpretation.